Rhythm and clues - Blacke, Olivia (Blacke, Olivia. Record shop mysteries., 2024)
"It's been five whole months since the last murder in Cedar River, Texas, and Juni Jessup and her sisters Tansy and Maggie have been humming along when disaster strikes again. Their struggling vinyl records shop/coffee nook, Sip & Spin Records, is under pressure from predatory investors, though the Jessup sisters aren't ready to face the music and admit defeat. But the night after their meeting, the sketchy financier is killed outside their shop during a torrential Texas thunderstorm that washes out all the roads in and out of town. Now the sisters find themselves trapped in Cedar River with a killer, and Juni is determined to solve the case. When the river spits out an unexpected surprise, Detective Beau Russell asks for Juni's help, never predicting her investigation will spin her into danger. Up until now, the Jessup sisters have been playing it by ear, but with the whole town watching, can they catch a killer before he strikes again?"--Amazon.